2020
DOI: 10.1002/cncr.32747
|View full text |Cite
|
Sign up to set email alerts
|

En bloc retroperitoneal laparoscopic radical nephrectomy with inferior vena cava thrombectomy for renal cell carcinoma with level 0 to II venous tumor thrombus: A single‐center experience

Abstract: BACKGROUND:The surgical treatment of patients with renal cell carcinoma (RCC) with venous tumor thrombus (VTT) is challenging. In the current study, the authors have reported their surgical outcomes and experience with en bloc retroperitoneal laparoscopic radical nephrectomy (LRN) with inferior vena cava (IVC) thrombectomy for patients with RCC with level 0 to II VTT. METHODS: A retrospective review of the clinical records of 78 patients who underwent retroperitoneal LRN with IVC thrombectomy from March 2015 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…All surgeries were performed for curative purpose. The surgical steps of radical nephrectomy and thrombectomy in our center were described in the previous publication (32), but we performed radical nephroureterectomy and thrombectomy when preoperative diagnosis was UC. For level-0 TT, renal vein was clamped before the entrance to IVC.…”
Section: Patientsmentioning
confidence: 99%
“…All surgeries were performed for curative purpose. The surgical steps of radical nephrectomy and thrombectomy in our center were described in the previous publication (32), but we performed radical nephroureterectomy and thrombectomy when preoperative diagnosis was UC. For level-0 TT, renal vein was clamped before the entrance to IVC.…”
Section: Patientsmentioning
confidence: 99%
“…The techniques of LRN-VT and ORN-VT at our institution have been described previously [8,[12][13][14]. For LRN-VT, both transperitoneal approach and retroperitoneal approach were used in our center depending on the thrombus level, tumor side, surgery history and invading the IVC wall or not.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…For level II thrombus, Wang et al [22] reported the surgical outcomes of laparoscopic procedure in 5 patients and found that 1 patient required intraoperative transfusion and encountered bilateral lower limb deep vein thrombus. Tian et al [8] once presented our laparoscopic experience in 78 patients with level 0-II thrombus and found that 24 patients (30.8%) needed transfusion and 13 patients (16.7%) had complications. Of the 94 patients in our matched LRN-VT cohort, 38 (40.4%) patients needed transfusion and 20 patients (21.3%) had Clavien I-IV complications.…”
Section: Lrn-vt(n = 94) Orn-vt(n = 94) P Valuementioning
confidence: 99%
See 1 more Smart Citation
“…The detailed steps of RPL-RN for left RCC were described in our previous report [16]. The difference is that after the left nephrectomy, the peritoneum should be incised about 10cm at the left paracolic sulci, preparing for the take of the specimen.…”
Section: Retroperitoneal Laparoscopic Left Rn (Rpl-rn)mentioning
confidence: 99%